2020
DOI: 10.3390/su12072976
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Invariance, Latent Mean Differences of the Panas and Affective Profiles and Its Relation to Social Anxiety in Ecuadorian Sample

Abstract: Positive (PA) and negative affect (NA) are related with aspects that are part of people’s psychological well-being, and the possibility of combining both dimensions to create four affective profiles, self-fulfilling (high PA and low NA), low affective (low PA and low NA), high affective (high PA and high NA) and self-destructive (low PA and high NA), has recently appeared. The current work aims to validate the short version of the Positive and Negative Affect Schedule (PANAS) in Ecuador, test the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
4
14
0
Order By: Relevance
“…Therefore, these statements are consistent with the relationships identified in other studies between high negative affect and low positive affect and anxiety and/or depression (Anderson et al, 2010;Domaradzka and Fajkowska, 2019). Similar results were seen in the work of Sanmartín and collaborators, where the self-destructive profile scored significantly higher on the first three SRAS-R-C factors, compared to the other profiles (Sanmartín et al, 2018a), and had higher scores for social anxiety (Sanmartín et al, 2020). These findings would also be in line with the data provided from the studies by Higa et al (2002), Gonzálvez et al (2016), andInglés et al (2016), where significant correlations were found between negative affect and the first three SRAS-R-C factors.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, these statements are consistent with the relationships identified in other studies between high negative affect and low positive affect and anxiety and/or depression (Anderson et al, 2010;Domaradzka and Fajkowska, 2019). Similar results were seen in the work of Sanmartín and collaborators, where the self-destructive profile scored significantly higher on the first three SRAS-R-C factors, compared to the other profiles (Sanmartín et al, 2018a), and had higher scores for social anxiety (Sanmartín et al, 2020). These findings would also be in line with the data provided from the studies by Higa et al (2002), Gonzálvez et al (2016), andInglés et al (2016), where significant correlations were found between negative affect and the first three SRAS-R-C factors.…”
Section: Discussionsupporting
confidence: 90%
“…This result would be, to some extent, supported by the negative and significant correlations between positive affect and the first two SRAS-R-C factors found in the study by Gonzálvez et al (2016). Likewise, this finding is indirectly supported by the research carried out with adolescents Sanmartín et al, 2020) in which it was observed that the adolescents with the self-fulfilling profile showed lower scores in depressive symptoms and social anxiety, psychological variables related to school refusal behavior in these first two SRAS-R-C factors.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations